(untitled) (Revista Innova Educación, 2023)
The objective of this study was to know the perception of harassment and sexual harassment of the students of a public university in Huancavelica, Peru. The study corresponds to a basic investigation with a non-experimental design and of a descriptive nature. The population was made up of 3603 students of 19 professional careers enrolled in the year 2021, from which a probabilistic sample was extracted. The instrument "Relations that violate the rights of people" by Bardales and Ortiz (2012) adapted to the Huancavelican reality was used. It was identified that 28% of university students have suffered harassment or sexual harassment, mostly women, mostly they have suffered demands for sexual relations and offensive comments, the aggression has been received by strangers and in public spaces. It was also found that the analyzed university complies by providing prior information on the actions to be taken in the face of this type of behavior, however, in careers related to engineering there is greater patriarchal thinking. These results, products of the study at this university, constitute a cut-off point in the broad study of gender violence in the Peruvian university system, a study in particular, and a setting on the academic stage of the university reality.